Prevalence of chronic obstructive pulmonary disease (COPD) and its associated factors among adults in Abeshge District, Ethiopia: a cross sectional study - Woldeamanuel, Gashaw Garedew (BMC Pulm Med, 2019)
BACKGROUND: Chronic obstructive pulmonary disease (COPD) is one of the major public health problems worldwide. Despite an increasing burden of COPD in the world, it is often a neglected disease in low income countries and COPD prevalence studies are rare in Sub-Saharan Africa. The objective of this study was to determine the prevalence of COPD and its associated factors among adults in Ethiopia. METHODS: A community based cross sectional study was conducted from February 5 to May 20, 2019 in Abeshge district, Southern Ethiopia. A total of 734 adults aged at least 30 years were selected using multistage cluster sampling technique and included in the study. All participants were interviewed about socio-demographic characteristics, respiratory symptoms, smoking status and clinical characteristics. Moreover, all participants underwent spirometry. We defined COPD as a post-bronchodilator FEV1/FVC of less than 70%. Data were entered into Epi-data manager 4.4 and analyzed using SPSS version 23. Descriptive statistics and binary logistic regression analysis were used and p-value < 0.05 was considered as significant. RESULTS: Of the 779 adults invited to participate, 734 adults (421 men and 313 women) were participated in this study. The mean (SD) age of the participants was 39.15 (± 9.36) years, within the age range of 30–75 years. The prevalence of COPD was 17.8% (95% confidence interval [CI], 15.1–20.6). Factors significantly associated with COPD were age above 50 years (adjusted odds ratio [AOR] = 1.91, 95% CI [1.10, 3.30]), being smoker (AOR = 4.54, 95% CI [2.69, 7.66]), Exposed to biomass smoke (AOR = 2.05, 95% CI [1.06, 3.95]) and poor ventilated kitchen (AOR = 4.12, 95% CI [2.67, 6.34]). CONCLUSION: It is evident from this study that the prevalence of COPD in Ethiopia is high. Factors such as old age, cigarette smoking, exposure to biomass smoke and poor kitchen ventilation plays a role in the development of COPD.